Pediatric Ophthalmology, Neuro-Ophthalmology, Genetics Strabismus - New Concepts in Pathophysiology, Diagnosis, and Treatment - Lorenz, Birgit; Brodsky, Michael C. (Essentials in Ophthalmology,, 2010)
The 8 recurring volumes of the "Essentials in Ophthalmology" series cover the most recent developments in one of eight subspecialties in Ophthalmology. With four volumes published per year, each subspecialty is newly visited every 24 months, with a distinct focus on recent developments. By bridging the gap between original research and medical textbooks, the transfer of this developing knowledge into daily practice is greatly enhanced.